Sociocultural Byzantine Influence on Thought Formation in Medieval Russia - Revko-Linardato , Pavel (Peitho. Examina Antiqua, 2014)
The Byzantine influence was at the very origins of the formation of various philosophic ideas in the medieval Russia. A major factor responsible for this influence was the Orthodox Church. Thus, it was owing to Byzantium that the foundations of Russian philosophy were laid and all its subsequent developments cannot be properly understood without considering the Byzantine influence.